Unilateral lattice corneal dystrophy in a young female: A unique case report - Raj, Anuradha; Dhasmana, Renu; Bahadur, Harsh (Nepalese Journal of Ophthalmology, 2017)
Background: Unilateral lattice corneal dystrophy is a rare entity. Objective: To highlight the evidence of unilateral lattice corneal dystrophy in a young female. Case: A young 28 years old female presented to the outpatient department of Ophthalmology with slowly progressive diminution of vision in left eye for one month. On ophthalmological examination best corrected visual acuity (BCVA) was 20/20 and 20/40 with refractive error of plano and -0.75D Cyl @30 for right and left eye respectively. Ocular examination of right eye was unremarkable. On slit lamp examination, left eye showed multiple radial lattice lines in branching spider like pattern in the temporal cornea with pupillary margin involvement. The lattice pattern was confined to anterior to midstroma of the cornea with intact epithelium and unremarkable endothelium. The lesions did not involve the limbus. These lattice lines were prominent on retroillumination. In temporal quadrant near pupillary margin a small radial nebulomacular corneal opacity was seen without any corneal vascularisation or edema. The anterior chamber was deep and quiet. Corneal sensations were markedly reduced. Intraocular pressure was 10 and 12mmHg for right and left eye respectively with noncontact tonometry. Fundus examination was unremarkable. Family history and systemic history was negative. Optical coherence tomography(OCT) showed hyperreflective material in midstoma confirmed the diagnosis of unilateral lattice corneal dystrophy(LCD) with an apparently healthy fellow eye.